Rapid Photocrosslinkable Thermoresponsive Injectable Polyphosphazene Hydrogels - Potta, Thrimoorthy; Chun, ChangJu; Song, Soo-Chang (WILEY-V C H VERLAG GMBH, 2010)
Rapidly photocrosslinkable and thermosensitive polyphosphazene polymers have been prepared to overcome the limitations associated with long UV exposure. Short UV exposure on the thermosensitive gels under mild conditions leads to quick photocrosslinking of the acrylate groups in the polymer network, and results in a dual crosslinked network with enhanced mechanical strength. The accelerated photocrosslinking can be attributed to the high reactivity of the acrylate double bond and hydrophobic interactions in the polymer network. The effects on the degree of photocrosslinking of the UV light intensity and the concentration of the photoinitiator were studied. In vitro and in vivo photocrosslinkings were accomplished within 120 and 180 s of exposure times, respectively. The degradation rate of the polymers depended on the degree of acrylate substitution in the polymer network. These results demonstrate that the injectable hydrogels with desired mechanical properties and degradation rates can be created in situ under mild photocrosslinkable conditions, and the dual crosslinkable acrylated poly(organophosphazenes) may hold great promise for biomedical delivery applications of biological molecules, cells, and drugs.
Keywords: TRANSDERMAL PHOTOPOLYMERIZATION; DRUG-DELIVERY; RELEASE; COPOLYMER; ALCOHOL)